Development of Moroccan oasis: Theoretical inputs and practical outputs. Daraa-Tafilalet model - KRIMI , Abdelkrim (Social Empowerment Journal, 2020)
Moroccan oasis has been living for decades in a worrying situation that indicates the accelerating consequences of the various environmental risks that threaten this area. In addition to the growing efficiency of wind dynamics, the phenomenon of desertification, with its various manifestations of sand creep, is exacerbated...The oasis basins are also known annually as strong floods that affect the oasis and the community. In exchange for these calendars, oasis domains have a number of natural, human and heritage qualifications that can be mobilized and valued by creating a dynamic of development that promotes oasis and protects their fragile balances. In this regard, the preservation of ecological, economic, social and cultural services provided by the coastal area and by the national soil as a natural barrier to désertification, an important biological diversity incubator, an element of the climate balance, and a source of agricultural products with a highly specific nature; In addition to embracing a rich and diverse value system ... Top importance. Hence, the priority of identifying the inputs and outputs of the inspired development is to avoid the inconsistency and incomplementarity of public interventions and to establish an integrated approach to the problems of these rich and fragile areas.